Ownership Identification and Signaling of Multimedia Content Components - Ch., Sai Lakshman; .M.S, Saravanan (International Journal of Psychosocial Rehabilitation, 2020)
We are proposing a new concept for large-scale, interactive content protection systems in this paper. Our architecture leverages cloud infrastructures to deliver cost-effectiveness and fast deployment with some additional attributes to improve the security of content. The framework proposed could be used to secure various forms of multimedia content, including 2-D videos, 3-D videos, photographs, audio clips, songs, and music clips. The content of the multimedia can be used in different approaches to implement security with various components such as videos, audio files, etc. These types of contents are deployed on private or public clouds. The signature method has the unique nature of 3D video representation with a signature-based approach. At the same time, efficient computational methods are used for depth signaling. With the high scalability and efficient methods to protect multimedia objects, in this paper we propose a signature-based approach using a cloud framework.